STUDY ON STIFFNESS COEFFICIENTS UNDER BENDING TEST OF END CORNER DETACHABLE JOINTS OF STRUCTURAL ELEMENTS MADE OF PLYWOOD - Simeonova, Ralitsa; Marinova, Assia; Jivkov, Vassil (Innovation in Woodworking Industry and Engineering design, 2015)
In this study are given the results from investigation into stiffness of end corner detachable joints of structural elements made of beech veneer plywood. The stiffness coefficients under compression bending test have been determined. The highest stiffness is characteristic of joints with universal connector and screw for wood ø 6 х 90 and ø 6 х 80 mm while the lowest stiffness is typical of joints with Minifix with bolt, mounting in metal sleeve and direct mounting. The parameters of the screw joints have considerable impact on the stiffness characteristics of the joints. It is recommended that the comparative data of bending strength be taken into consideration when selecting the type of joints in the construction of furniture made of plywood.